What Is The Prevalence of Acute Cardiovascular Events among Elderly Hajj Pilgrims (≥60 Years), and What are The Associated Risk Factors? : A Systematic Review - Hafiz Anugrah Mursyid; Yessica Sheila Sitompul (The International Journal of Medical Science and Health Research, 2026)
Introduction: The Hajj pilgrimage, attracting millions of Muslims annually, involves elderly participants (≥60 years) who face significant cardiovascular risks due to advanced age, comorbidities, and extreme environmental conditions. Despite cardiovascular disease being the leading cause of Hajj-related mortality, the precise prevalence of acute cardiovascular events among elderly pilgrims and their associated risk factors remain poorly quantified. This systematic review aimed to determine the prevalence of acute cardiovascular events among elderly Hajj pilgrims (≥60 years) and identify associated risk factors. Methods: A systematic review of 58 observational studies, systematic reviews, and meta-analyses was conducted. Studies were included if they involved Hajj pilgrims aged ≥60 years, reported cardiovascular outcomes during the Hajj period, and provided quantifiable data. Data extraction focused on study characteristics, elderly pilgrim demographics, cardiovascular event definitions, prevalence rates, and risk factor associations. Data sources included SISKOHATKES (Indonesian Hajj health information system), hospital records, and mortality registries. Results:  Mortality data showed that 81% of Hajj deaths occurred in pilgrims ≥60 years (3), with cardiovascular causes accounting for 38-42% of all deaths (1,2). Cardiovascular risk factor prevalence among elderly pilgrims was extremely high: hypertension (71.34%), hyperglycemia (43.76%), and hypercholesterolemia (59.46%) (8). Age ≥60 years was the dominant risk factor for mortality (adjusted OR range: 3.1–8.1) (3,10,11). Diabetes mellitus showed the strongest association with mortality in some cohorts (RRa=18.7) (3), while hypertension (OR=2.03–3.7) (3,10,13), dyslipidemia (OR=1.82) (13), and male gender (OR=1.87) (10) were consistently significant. Hajj-specific factors, including heat stress (independent predictor of MACE, p=0.001) and dehydration (independent predictor of mortality, p=0.009) (15), emerged as critical triggers. High-risk health status (risti) classification demonstrated strong associations with mortality (OR=7.83) (27) and morbidity (Exp(B)=19.745) (40). Discussion: The cardiovascular burden in elderly Hajj pilgrims results from a convergence of high comorbidity prevalence, age-related physiological vulnerability, and extreme environmental stressors. The absence of direct prevalence estimates reflects methodological limitations in current surveillance systems. The interaction between traditional risk factors and Hajj-specific triggers—particularly heat exposure during the physically demanding Armuzna (Arafah, Muzdalifah, Mina) phase—provides a mechanistic framework explaining both elevated baseline risk and annual mortality variability. The paradoxical finding that AMI pilgrims had worse outcomes despite fewer traditional risk factors (19) underscores the importance of environmental triggers. The extreme diabetes-related mortality risk in 2023 likely reflects synergistic effects of heat stress and operational failures. Integrated risk stratification using functional capacity (6MWT) and composite high-risk classification offers the most evidence-based screening approach. Conclusion: Elderly Hajj pilgrims face a 3- to 8-fold increased mortality risk compared to younger pilgrims, driven primarily by cardiovascular disease in the context of near-universal risk factor burden. Pre-departure screening should prioritize integrated risk assessment incorporating age, comorbidities, and functional capacity, while during-Hajj interventions must focus on heat exposure mitigation and early recognition of cardiovascular events in this vulnerable population.